LOYALITAS KONSUMEN DALAM MENINGKATKAN OMZET PENJUALAN PADA GERAI INDOMARET DI KECAMATAN LOCERET KABUPATEN NGANJUK - Intan Dameria (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2016)
Transactions sell and buy can not be separated from human life. due to the increasingly growing modernization of transactions, the transaction also experienced a development. thus the term modern market was born (Sinaga, 2006). the modern market is a market managed by modern management, generally in urban areas, as a provider of goods and services with good quality and service to consumers who are generally members of middle and upper class society. Indomaret as one example of the modern market that has grown in the community take part in the fulfillment of consumer needs. The high public interest towards the modern market caused indomaret to become one of the best-selling mini-marketers. the world of business is always related to the term turnover and profit, not infrequently people still misunderstand between turnover and profit. Some understand between turnover and profit in reverse or even equate it. Omzet referred to in this study is the value of all the money earned business results of product sales. Turnover is all money coming in, in layman language is called gross income. because turnover is a gross income, where it still has to calculate the cost of goods, as well as other expenses to earn residual income as profit. the definition of customer satisfaction is as a full-time evaluation where the selected alternatives at least equal or exceed customer expectations, while dissatisfaction arises if the results do not meet customer expectations so that consumers who feel satisfied with the services provided a company will re-purchase goods or services in the company. So that will bring customer loyalty. Customer loyalty is an in-depth customer commitment to re-subscribe or re-purchase consistent products / services consistently in the future, although the influence of the marketing situation and efforts has the potential for behavioral change (Oliver, 2000 in Ratih Hurriyanti, 2005). This study aims to describe the role between the increase in turnover in retail business (Indomart) with customer loyalty. This study also aims to provide an overview of the development and increase of sales turnover in retail business. The research method used in this research is using qualitative narrative approach. Where in this type of research focuses on the experience experienced by a person or an organization. the findings in this study obtained a model that loyalty customers increase sales turnover in retail business indomart.